Perancangan Sistem Informasi Point of Sale (POS) Berbasis Web untuk Mendukung Pengelolaan Kasir dan Manajemen Meja pada D'S CAFE FAMILY & KITCHEN - Syandhika Ahmad Farroja; Farizi Ilham; Rizky Koto (BINER : Jurnal Ilmu Komputer, Teknik dan Multimedia, 2026)
The rapid advancement of information technology has encouraged businesses in the food and beverage sector to adopt digital systems that improve operational efficiency and service quality. D'S CAFE FAMILY & KITCHEN currently faces challenges in managing sales transactions and monitoring table availability due to the lack of an integrated system. This study aims to develop a web-based Point of Sale (POS) information system that integrates cashier transactions with table management to support daily operational activities more effectively. The system was developed using the Waterfall software development methodology, which consists of requirements analysis, system design, implementation, testing, and maintenance. The application was developed using PHP, MySQL, and XAMPP, while system functionality was evaluated through Black Box Testing. The implementation results indicate that the developed system is capable of managing user data, menu items, sales transactions, payments, table availability, and sales reports within a single integrated platform. In addition, the system provides real-time table status information, enabling faster customer service, more efficient transaction processing, and improved operational management at D'S CAFE FAMILY & KITCHEN.